ECCO Topical Review on Clinicopathological Spectrum and Differential Diagnosis of Inflammatory Bowel Disease. (4th August 2021) - Feakins, Roger; Torres, Joana; Borralho-Nunes, Paula; Burisch, Johan; Cúrdia Gonçalves, Tiago; De Ridder, Lissy; Driessen, Ann; Lobatón, Triana; Menchén, Luis; Mookhoek, Aart; Noor, Nurulamin; Svrcek, Magali; et al.
Abstract: Introduction: Many diseases can imitate inflammatory bowel disease [IBD] clinically and pathologically. This review outlines the differential diagnosis of IBD and discusses morphological pointers and ancillary techniques that assist with the distinction between IBD and its mimics. Methods: European Crohn's and Colitis Organisation [ECCO] Topical Reviews are the result of an expert consensus. For this review, ECCO announced an open call to its members and formed three working groups [WGs] to study clinical aspects, pathological considerations, and the value of ancillary techniques. All WGs performed a systematic literature search. Results: Each WG produced a draft text and drew up provisional Current Practice Position [CPP] statements that highlighted the most important conclusions. Discussions and a preliminary voting round took place, with subsequent revision of CPP statements and text and a further meeting to agree on final statements. Conclusions: Clinicians and pathologists encounter a wide variety of mimics of IBD, including infection, drug-induced disease, vascular disorders, diverticular disease, diversion proctocolitis, radiation damage, and immune disorders. Reliable distinction requires a multidisciplinary approach.